2017
DOI: 10.1177/2059436418756096
|View full text |Cite
|
Sign up to set email alerts
|

Framing China: Discourses of othering in US news and political rhetoric

Abstract: China has emerged in the early 21st century as arguably the most important partner and rival to the United States. Increasingly, the United States perceives China's rise on the world stage as a threat to US global hegemony. US national discourse has constructed China, we argue, as a potential enemy Other-an ever-present threat with whom we cautiously partner with.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Even, the media reports shape the nature of the relationship. Valuation of Chinese national currency and its cyber espionage adventurism were the frequent themes in US news media determining the nature of US-China relationship according to Ooi and D'arcangelis (2017). These results show that the impact of media may be felt in shaping the public perception as well as government policies.…”
Section: Discussionmentioning
confidence: 79%
“…Even, the media reports shape the nature of the relationship. Valuation of Chinese national currency and its cyber espionage adventurism were the frequent themes in US news media determining the nature of US-China relationship according to Ooi and D'arcangelis (2017). These results show that the impact of media may be felt in shaping the public perception as well as government policies.…”
Section: Discussionmentioning
confidence: 79%
“…To be more precise, it is the liberal disavowal of Sinophobia that will not be the same as the pandemic exposes liberalism's long tradition of complicity with xenophobia and modern empire-building (Lowe 2015). There is certainly a discontinuous yet interconnected genealogy of dominant Sinophobic tropes in the West-from the Yellow Peril of a decaying dynasty, to the Red Scare of a brainwashing Communist regime, to the neo-Orientalist struggle against an authoritarian superpower (Yang 2010;Gries 2014;Ooi and D'Arcangelis 2018;Visco 2019). With this genealogy in mind, I would suggest that Covid-19 has intensified a preexisting trend of Cold War ideological opposition to China to the degree that dominant-both conservative and progressiveliberal-discourses in the West have stopped expecting the country 'to be normal like us ', which Daniel Vukovich (2012, 23) calls 'the becoming logic'.…”
Section: Ruptures and Continuitymentioning
confidence: 99%
“…As an emerging power with the world's biggest population, China has been receiving increasing amounts of attention in the Western media. Since the Communist Party seized power in 1949, the framing of contemporary China has been associated with Sino-Western relations, and "friend and foe frames" have been prevalent in the Western media (Stone & Xiao, 2007;Golan & Lukito, 2015;Ooi & D'Arcangelis, 2018). In their review of the coverage in American magazines of Mao Zedong and China under his rule during the Cold War, Yu, and Riffe (1989) found that the framing of Mao's China was closely correlated to the development of Sino-Western relations.…”
Section: Framing China By Western Mediamentioning
confidence: 99%
“…In the past, research on the framing of China by media in the West has yielded insightful findings and revealed similar patterns, such as the enduring "friend versus enemy" frame (Stone & Xiao, 2007;Golan & Lukito, 2015;Ooi & D'Arcangelis, 2018). However, the framing of the West by Chinese media has not yet been fully explored.…”
mentioning
confidence: 99%